INFLUENCE OF MINERAL NUTRITION ON THE SOIL HEALTH AND PRODUCTIVITY OF COCONUT PALMS (Cocos nucifera L.) IN TROPICAL LAND USE SYSTEMS - Abdulkadir Keskin; Irfan Ersin; Abdulkadir Atalan (Journal of Animal and Plant Sciences, 2024)
Perennial plantation crops, such as coconut trees require the systematic addition of nutrients for sustained growth and productivity.  This study aimed to understand plant and soil nutrient dynamics, root health and soil biological properties upon addition of specific nutrients in tropical land use systems. Field experiments in randomised block design were conducted in Agro-Ecological Unit-3 (AEU-3) and Agro-Ecological Unit-9 (AEU-9) from 2014 to 2020. Treatments were T1 (site-specific nutrient management practices (SSNM), T2 (SSNM without sodium chloride); T3 (SSNM without gypsum); T4 (SSNM along with the 50 g microbial formulation Kera Probio); T5 (Farming practice without any amendments or nutrients). Root health parameters, cumulative nut yield and nutrient dynamics in soil and leaf samples were estimated at the beginning and the end of the study.  Systematic provision of all the essential nutrients resulted in significant increase content of N (1.39%), P (0.164%), K (1.71%), Ca (0.406%) and Mg (0.175%) in index leaves of coconut trees in sandy soils. Foliar nutrient levels of coconut trees grown in laterite soils were 1.21% N, 0.142% P, 1.27% K, 0.504% Ca and 0.146% Mg. In AEU-3, treatment that received all amendments and nutrients showed highest organic carbon content at the three depths as 6.79 g kg-1soil, 5.39 g kg-1 soil and 3.82 g kg-1, soil, respectively. In AEU-3, 61% increase in yield was observed, while in AEU-9,40% increase was recorded. Application of gypsum resulted in downward displacement of K and Mg indicating that gypsum is   required for the amelioration of sub soil acidity in sandy soils. However, the displacement effect was less pronounced in laterite soils and beneficial effect of gypsum was evident with the enhancement of exchangeable Ca. Hence sandy soils require application of inputs as per T3 (T1 without gypsum), with external organic inputs and palm residues whereas in laterite soils application of treatments as per T1 is required with in situ palm residue recycling.
Keywords: coconut; leaf nutrients; sandy soil; laterite soil; root health; dehydrogenase